The effects of bentonite on rumen protozoal population and rumen fluid characteristics of sheep fed palm kernel cake - Abdullah, Norhani; H., Hanita; Ho, Yin Wan; Kudo, Hiroshi; Jalaludin, S.; Ivan, Michael (Asian-Australasian Association of Animal Production Societies, 1995)
The effects of bentonite (B) on rumen protozoal population and rumen fluid characteristics of sheep fed palm kernel cake (PKC) were studied for a period of 21 days. Two groups, each comprising two sheep were fed either PKC or PKC + B ad libitum. A third group was left at pasture. Rumen fluid was sampled through a rumen cannula three times daily from all animals. Palm kernel cake contained 16% crude protein, 1% crude fat and high amounts of copper, zinc, iron and manganese. Protozoal population in the rumen fluid decreased significantly (p<0.05) after the onset of feeding PKC or PKC + B. However, sheep given bentonite supplementation at 2% of the dietary dry matter, maintained higher protozoal densities (15 x 104/ml) when compared to animals fed only PKC (8 x 104/ml). With both diets, the protozoa were mainly of the small entodinia species. Animals at pasture had higher protozoal population (47x 104/ml) with varying species of entodiniomorphids and holotrichs. Rumen fluid pH and ammonia concentration was significantly (p<0.05) higher in animals at pasture compared to animals fed PKC or PKC + B. Volatile fatty acid concentration was significantly (p<0.05) lower in animals fed PKC when compared to animals at pasture. There was a shift in fermentation pattern in animals fed PKC or PKC + B towards a lower acetate; and higher propionate, isovalerate and valerate. Studies in vitro also showed the positive effect of bentonite on protozoal numbers.